ÇEVRE EĞİTİMİ İÇİN KÜLTÜREL BİR BAKIŞ AÇISI: DEDE KORKUT HİKÂYELERİ. - DERMAN, Ayşegül; ASLAN, Zeynep (Electronic Turkish Studies)
Oral culture heritage filters national identity formation, common values in social memory and basic culture codes and brings them to the future generations. The book of Dede Korkut, which displays Turkish belief and thought systems, philosophy and viewpoint of life, could be accepted as an encyclopedia of culture because it carries the traces of Turkish old beliefs. The purpose of the current study is to analyze Dede Korkut stories in terms of environmental education and present a cultural viewpoint to the pedagogy of environmental education. This study applied qualitative research method. The data source was comprised of twelve stories in the book of Dede Korkut. Document analysis was applied to analyze the stories. Each story was analyzed according to the categories as elements of nature, living with nature in harmony, natural features attributed to human beings and human features attributed to natural assets. As a result of the analyses, a great number of various nature elements were determined in all Dede Korkut stories. A great number of samples for each category were determined and coded, and then these codes were interpreted in terms of Turkish mythology, belief systems and culture. The results showed that Dede Korkut stories could be used in environmental education to transfer our cultural point of view and cultural codes to the next generations. Dede Korkut stories could be used in environmental education by creating socio-cultural contexts appropriate for environmental subjects. It is thought that teaching environmental subjects in this way will contribute to teacher candidates, teenagers and also children's affective features such as loving, giving value, having interest and appreciating the natural assets. Furthermore, tertiary level students could be made to realize the perception of nature in these stories by examining Dede Korkut stories through holistic content analysis. Dede Korkut stories are good sources for studies dealing with cultural effects on environmental education.